The Evolving Concept of (Language) Assessment Literacy. Implications for Teacher Education - Csépes, Ildikó (Central European Journal of Educational Research, 2021)
Language teachers’ assessment knowledge and skills have received considerable attention from language assessment researchers over the past few decades (Davison & Leung, 2009; Hill & McNamara, 2012; Rea-Dickins, 2001; Taylor, 2013). This seems to be linked to the increased professionalism expected of them in classroom-based assessments. However, teachers seem to face a number of challenges, including how large-scale standardized language exams influence their classroom assessment practices. Teachers’ assessment literacy, therefore, needs to be examined in order to explain their assessment decisions. In this paper, we review the concept of (language) assessment literacy, how it has evolved and how it is conceptualized currently. Recent interpretations seem to reflect a multidimensional, dynamic and situated view of (language) assessment literacy. Implications for teacher education are also highlighted by presenting research findings from studies that explored teachers’ and teacher candidates’ assessment literacy in various educational contexts. As a result, we can identify some common patterns in classroom assessment practices as well as context-specific training needs. Finally, we make a recommendation for tackling some of the challenges language teachers are facing in relation to classroom-based assessment in the Hungarian context.